Psychological factors contributing to the creation and dissemination of fake news among social media users: a systematic review - Shalini Munusamy; Kalaivanan Syasyila; Azahah Abu Hassan Shaari; Muhammad Adnan Pitchan; Mohammad Rahim Kamaluddin; Ratna Jatnika (BMC Psychology)
Abstract The proliferation of fake news on social media platforms has become a significant concern, influencing public opinion, political decisions, and societal trust. While much research has focused on the technological and algorithmic factors behind the spread of misinformation, less attention has been given to the psychological drivers that contribute to the creation and dissemination of fake news. Cognitive biases, emotional appeals, and social identity motivations are believed to play a crucial role in shaping user behaviour on social media, yet there is limited systematic understanding of how these psychological factors intersect with online information sharing. Existing studies tend to focus on individual aspects of fake news consumption, such as susceptibility to misinformation or partisan biases, leaving a gap in understanding the broader psychological mechanisms behind both the creation and dissemination of fake news. This systematic review aims to fill this gap by synthesizing current research on the psychological factors that influence social media users’ involvement in dissemination and creation of fake news. Twenty-three studies were identified from 2014 to 2024 following the PRISMA guidelines. We have identified five themes through critical review and synthesis of the literature which are personal factors, ignorance, social factors, biological process, and cognitive process. These themes help to explain the psychological factors contributing to the creation and dissemination of fake news among social media users. Based on the findings, it is evident that diverse psychological factors influence the dissemination and creation of fake news, which must be studied to design better strategies to minimize this issue.